How do Intellectual Capital and Islamic Values Relate to Small Business Performance? A Conceptual Framework - Ahmad Azrin, Adnan; Sakinah, Mat Zin (2016)
There is a plethora of studies exploring the contributing factors to small business success based on the institution, financing and loan repayment, yet paying little attention to the intangible assets and Islamic values of the enterprises. Thus, these studies were seen inadequate to educate small entrepreneurs on how to attain competitive advantages and growth, eventually tocope with the global world. Only firms with ability in all aspects of competitive edges will be able to gain advantages over their rivals. Hence, the creation and management of intangible assets such as intellectual capital and Islamic values are vital to overcome firm competitiveness and performance issues. What components of intellectual capital that should be emphasized to gain a competitive edge and profitability? Do Islamic values predict the subsequent performance of small firms? Building on previous research, this paper may provide a deeper understanding of the relationships between intellectual capital, Islamic values and firm performance. Specifically, a conceptual model is developed linking different dimensions of intellectual capital and Islamic values to small business performance. This is then used to provide insights into how these 2 factors affect firm performance.